2009
DOI: 10.1105/tpc.109.071795
|View full text |Cite
|
Sign up to set email alerts
|

DGAT1andPDAT1Acyltransferases Have Overlapping Functions inArabidopsisTriacylglycerol Biosynthesis and Are Essential for Normal Pollen and Seed Development  

Abstract: Triacylglycerol (TAG) biosynthesis is a principal metabolic pathway in most organisms, and TAG is the major form of carbon storage in many plant seeds. Acyl-CoA:diacylglycerol acyltransferase 1 (DGAT1) is the only acyltransferase enzyme that has been confirmed to contribute to TAG biosynthesis in Arabidopsis thaliana seeds. However, dgat1 null mutants display only a 20 to 40% decrease in seed oil content. To determine whether other enzymes contribute to TAG synthesis, candidate genes were expressed in TAG-defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
417
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 431 publications
(456 citation statements)
references
References 79 publications
24
417
1
1
Order By: Relevance
“…However, there was no significant impact on TAG accumulation in pdat1 loss-of-function mutants or in plants overexpressing A. thaliana PDAT, so the role in overall TAG accumulation in Arabidopsis was uncertain (61,62). A clear demonstration of a role for PDAT1 in TAG biosynthesis was provided more recently when its expression was silenced by RNA interference in a dgat1-1 mutant background (63). Seed TAG content was reduced by 70 -80%, and normal seed (and pollen) development was disrupted.…”
Section: Acyl-coa-independent Mechanisms Involved In Tag Synthesismentioning
confidence: 96%
“…However, there was no significant impact on TAG accumulation in pdat1 loss-of-function mutants or in plants overexpressing A. thaliana PDAT, so the role in overall TAG accumulation in Arabidopsis was uncertain (61,62). A clear demonstration of a role for PDAT1 in TAG biosynthesis was provided more recently when its expression was silenced by RNA interference in a dgat1-1 mutant background (63). Seed TAG content was reduced by 70 -80%, and normal seed (and pollen) development was disrupted.…”
Section: Acyl-coa-independent Mechanisms Involved In Tag Synthesismentioning
confidence: 96%
“…Previous studies have shown that overexpression of DGAT1 and WRI1 individually leads to enhanced oil accumulation in vegetative tissues (BouvierNavé et al, 2000;Cernac and Benning, 2004) and also that a synergistic effect is achievable when they are expressed in combination (Vanhercke et al, 2013). WRI1 is a transcription factor that activates the expression of genes encoding multiple enzymes primarily of lower glycolysis and fatty acid synthesis (Cernac and Benning, 2004;Baud et al, 2007), and DGAT1 is the major enzyme that catalyzes the final committed step in TAG synthesis (Katavic et al, 1995;Zhang et al, 2009).…”
Section: Disruption Of Sdp1 In Lines Expressing Wri1 and Dgat1 Leads mentioning
confidence: 99%
“…The dgat1-1 and pdat1-1 mutants are described by Katavic et al (1995) and Zhang et al (2009), respectively. For experiments performed on medium, seeds were surface sterilized, plated on agar plates containing one-half-strength Murashige and Skoog salts (Sigma-Aldrich) with or without the addition of Suc, and imbibed in the dark for 4 d at 4°C.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…In most seeds, the major lipid storage form is triacylglycerol (TAG), known to be produced by acyl-CoA: diacylglycerol acyltransferase (DGAT) and phospholipid:diacylglycerol acyltransferase (PDAT; Zhang et al, 2009). DGAT1 has been shown in Arabidopsis to be the major, but not the sole, enzyme to contribute to the accumulation of seed TAGs, working together mainly with PDAT (Zhang et al, 2009).…”
mentioning
confidence: 99%